Implementasi Kebijakan Penegakan Disiplin Protokol Kesehatan Masyarakat Distrik Mandobo Kabupaten Boven Digoel - Laiyan, David (Jurnal Administrasi Karya Dharma, 2023)
The handling of the Covid 19 pandemic has led to changes in lifestyle and health in society which has triggered a shift in the government's perspective in regulating the process of people's lives in accordance with ongoing conditions. This research was conducted with the aim of knowing the implementation of government policies regarding the discipline of public health protocols in the Mandobo District, Boven Digoel Regency using a qualitative descriptive method approach. The results of this study indicate that the implementation of government policies regarding discipline enforcement of public health protocols in Sokanggo Village, Mandobo District, Boven Digoel Regency has been running but has not been optimal because there are still people who lack awareness to comply with government regulations, namely by not wearing masks, not washing their hands and not maintaining distance. It can be seen from several indicators, namely on the communication indicator that the government has informed the importance of health protocols and outreach about complying with health protocols by wearing masks, washing hands and keeping a safe distance, providing mask assistance and outreach to the public about family health and has carried out outreach by distributing pamphlets about preventing the spread Corona Virus. It can also be seen from the attitude indicator that implementers have been given an appeal so that the community maintains health by following the discipline of health protocols and a healthy lifestyle. In the bureaucratic structure, the Sokanggo Village government has followed instructions by forming a Covid-19 Volunteer Team to serve the community according to their duties.